2015
DOI: 10.1007/s11695-015-1687-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Patients with Helicobacter pylori Undergoing Laparoscopic Sleeve Gastrectomy

Abstract: Our data suggests that there is no increase in early complications in patients with H. pylori undergoing VSG. If these findings are confirmed in a long-term follow-up, it would mean that preoperative H. pylori screening in patients scheduled for VSG is not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Some findings may vary according to geographic distributions. For example, the frequency of HP infections can vary from 3.2% to 64% (15)(16)(17)(18)(19)10,(20)(21)(22)(23). This rate was 35% in our series.…”
Section: Discussionmentioning
confidence: 47%
“…Some findings may vary according to geographic distributions. For example, the frequency of HP infections can vary from 3.2% to 64% (15)(16)(17)(18)(19)10,(20)(21)(22)(23). This rate was 35% in our series.…”
Section: Discussionmentioning
confidence: 47%
“…Recently, many studies indicated that gut microbiota plays a key role in maintaining host body homeostasis [1, 6]. Helicobacter pylori is an important member of the microbiome affecting >50% of the world population and is related to the development of diverse gastric and extragastric diseases, such as gastric cancer, chronic gastritis, gastric ulcers, and duodenal and peptic ulcers [7, 8]. The rates of H. pylori infection in obese patients with gastrointestinal disorders (GID) varies geographically.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, the number and seriousness of pathology diagnostics after bariatric surgery is substantial (17) mainly because of Helicobacter Pylori (HPyl) gastric infection. As after any gastric surgery, HPyl may also generate early post bariatric complications (18) fact that makes diagnostic and treatment of HPyl infestation, a priority (19).…”
Section: Introductionmentioning
confidence: 99%